FRAKSINASI MINYAK NILAM DENGAN REDISTILASI - , FARIDA ANA NOVIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The value of patchouli oil which is exported from Indonesia increasing every year. The development of cosmetic and parfume products in domestic market may lead to the raise of patchouli oil demand. The main component which influences the export value of the patchouli oil is patchouli alcohol. The higher the patchouli alcohol content, the higher the value. This study is carried out by using designated equipment to get high content of patchouli alcohol fraction and to get a few different composition fractions at a time of re-distillation in which simpler and more economical technology is being used. Patchouli oil has 5 levels of fractional re-distillated mixed with aquadest, comparation 1:5 (oil 1 and water 5 ). The mixture was heated. Then the distillation is carried out in level 1, 2, 3, and 4 in every 60 minutes. Then it is decantated using separate tubes. After a few moment, water can be separated from the oil. The remaining water is bound in Na2SO4,which is a sample. While 0- level is carried out at late heating. Then the volume of sample will be calculated and the patchouli alcoholâs content needs to be analyzed. This study uses two variables: Duration of Time (420, 300 and 180 minutes) and Temperature Temperature 100 0 C, 110 0 C). The observation is conducted in every fraction they got. When there is distinctive differences found, the datas will be analyzed with variable analysis (ANOVA) that will be followed by DMRT (Duncan Multiple Range Test). Based on the result of the above research, the conclusion is the durration of time is influencing the patchouli oil fractional process with re-distillation method to enhance the content of patchouli alcohol on patchouli oil. The patchouli alcohol content which is 38,83% on 4 th fraction as a result of 420 minutes heating, and result of 180 minutes heating of 0-fraction which is 65,17%. Influencing contribution to the pocess is given by temperature. The patchouli alcohol content which is 34,75% on 4 th fraction as a result of 110 0 C heating, and result of 100 0 C heating on 0-fraction is 50,99%.